Genome-wide association study identifies 19p13.3 (UNC13A) and 9p21.2 as susceptibility loci for sporadic amyotrophic lateral sclerosis - van Es, Michael A; Veldink, Jan H; Saris, Christiaan G J; Blauw, Hylke M; van Vught, Paul W J; Birve, Anna; Lemmens, Robin; Schelhaas, Helenius J; Groen, Ewout J N; Huisman, Mark H B; van der Kooi, Anneke J; de Visser, Marianne; et al. (Nature genetics, 2009)
Leonard van den Berg, Roel Ophoff and colleagues present a genome-wide association study of sporadic amyotrophic lateral sclerosis. The work uncovers associated SNPs at 9p21.2 and an associated locus at 19p13.3 mapping to the UNC13A gene. We conducted a genome-wide association study among 2,323 individuals with sporadic amyotrophic lateral sclerosis (ALS) and 9,013 control subjects and evaluated all SNPs with P < 1.0 × 10 −4 in a second, independent cohort of 2,532 affected individuals and 5,940 controls. Analysis of the genome-wide data revealed genome-wide significance for one SNP, rs12608932, with P = 1.30 × 10 −9 . This SNP showed robust replication in the second cohort ( P = 1.86 × 10 −6 ), and a combined analysis over the two stages yielded P = 2.53 × 10 −14 . The rs12608932 SNP is located at 19p13.3 and maps to a haplotype block within the boundaries of UNC13A , which regulates the release of neurotransmitters such as glutamate at neuromuscular synapses. Follow-up of additional SNPs showed genome-wide significance for two further SNPs (rs2814707, with P = 7.45 × 10 −9 , and rs3849942, with P = 1.01 × 10 −8 ) in the combined analysis of both stages. These SNPs are located at chromosome 9p21.2, in a linkage region for familial ALS with frontotemporal dementia found previously in several large pedigrees.